Politics and the press in Thailand : media machinations - McCargo, Duncan (Routledge, 2000)
This is the first book in English to examine the tangled web of relationships linking newspaper owners, editors and reporters, with leading politicians and power-holders.
Keywords: Press and politics -- Thailand.; LANGUAGE ARTS & DISCIPLINES -- Journalism.; Press and politics; Thailand; Massenmedien; Politik; Perswezen.; Journalistiek.; Politieke invloed.; Presse et politique -- Thaïlande.